Conflict, (Mis)Trust and Legal Pluralism in the Andean Region - Wolff, Jonas (2023)
During the last decades, the Andean region has moved significantly towards constructing systems of legal pluralism. This “work in progress”, however, has been and continues to be heavily contested in the judicial and the political sphere as well as within society at large. The article explores a theoretical perspective that emphasizes the relation between conflict and (mis-)trust in order to analyze the disputes about the legal recognition of indigenous justice and the establishment of legal pluralism in the Andean region. Based on existing studies and with a particular focus on the cases of Bolivia and Ecuador, four hypotheses are put forward: First, mistrust has been and is a key factor shaping the resistance against the recognition of indigenous justice. Therefore, second, a possible deconstruction of this mistrust requires open conflict that enables traditional elites and the general population to developan informed and differentiated opinion on the matter at hand. Third, however, such open conflict over indigenous justice can also contribute to reproducing, or even reinforcing, mistrust. Whether conflicts actually facilitate the deconstruction or rather the reproduction of mistrust depends, fourth, on the type of conflict and its articulation with broader socio-political controversies.